PERBANDINGAN PENDIDIKAN ISLAM DI INDONESIA DAN MALAYSIA - Budi Haryanto (Universitas Muhammadiyah Sidoarjo, 2015)
Islamic education as a subsystem which cannot be separated from national education, because it not only serves as a complement but also as the foundation stone for the formulation of national education goals. This is true in Indonesia and Malaysia. Islamic education in both countries, also affected the national struggle journey, to the efforts to maintain and develop its existence after the independence so as to have a clear role in mental strengthen human resources in their respective countries. This paper aims to examine the similarities and differences in the dynamics of the development of Islamic education in Indonesia and Malaysia in order to provide a complete understanding of the actualization of Islamic education since its first deployment to development in their respective countries to take shape more adaptive to the times. Benchmarks in this paper with a few descriptive reportorial ranges include a functional link to obtain a logical understanding of the reason for the implementation of the national education policy by using a historical approach.